Inaugural Address (The Pakistan Development Review, 1991)
Syed Nawab Haider Naqvi, Dr A. R. Kemal, Distinguished Guests, Ladies and Gentlemen: It is a matter of pleasure and privilege for me to inaugurate the Seventh Annual General Meeting of the Pakistan Society of Development Economists. I;un grateful to the President of the Society for his invitation to address this august body. I am pleased to observe that in its short but eventful existence the Society has grown in stature, nationally and internationally. It has contributed immensely to the cause of development economics and has deepened our understanding of the development process in Pakistan. The Society has carried out its task: in a low-keyed but efficient fashion, and has shown its commitment to achieving academic excellence. I wish to congratulate the Society for its accomplishments, with the sincere hope that it will continue to pursue its mission with undivided attention. This session of the Society is taking place at a crucial time. On the international front, the world is in the grip of a serious crisis emanating from the Gulf situation and the slowing down of world economic growth. And at home, despite many constraints the newly elected Government has embarked upon a bold programme of economic and social development and reforms.